AKTUALISASI BISNIS MULTI LEVEL MARKETING (MLM) DALAM RANAH SYAR’I - Agus Salim (LPPM IAI IBRAHIMY GENTENG BANYUWANGI, 2015)
Nowadays, Marketing company movement is developing rapidly. Multi Level Marketing or MLM company is a firm that applies the modern marketing system through gradual distribution network. It is built permanently by places the customer as its marketing staff. Multi Level Marketing (MLM) is not only a sale system that exploits its consumer as a direct distributor but also a consumer that has a gradual system suitable with his trial to reach the higher level. The marketing system of Multi Level Marketing (MLM) is by selling the company's product or just becomes the member. Based on Islamic opinion, the Multi Level Marketing (MLM) doesnt break the law if the sold product is